Development of innovative and creative on beauty and health packaging / Fatin Nur Nazifa Fathil - Fathil, Fatin Nur Nazifa (Universiti Teknologi MARA, Perak, 2020)
Creative packaging involves innovative designs and solutions that not only help products stand out above the rest, also to increase the product's growth and success. Candy Wax by RHEAAZURI is a local company selling 100% natural ingredients for instant hair removal products. The needs to further enhance the marketing of the product to ensure the sustainability of the company. The research develops an innovative printed solution with Augmented Reality (AR) integration. In addition, this process involved research on the identification of opportunities, exploration of concepts and refinement of printing processes. The outcome of these research is that the product quality is further improved by a box packaging with practical, value-added and impact-based innovation with integration of Augmented Reality (AR).